2005
DOI: 10.1002/cphc.200500246
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation Study of Ethyl Bromide in the Ultraviolet Range by the Ion‐Velocity Imaging Technique

Abstract: The photodissociation of ethyl bromide has been studied in the wavelength range of 231-267 nm by means of the ion velocity imaging technique coupled with a [2+1] resonance-enhanced multiphoton ionization (REMPI) scheme. The velocity distributions for the Br ((2)P(1/2)) (denoted Br*) and Br ((2)P(3/2)) (denoted Br) fragments are determined, and each can be well-fitted by a narrow single-peaked Gaussian curve, which suggests that the bromine fragments are generated as a result of direct dissociation via repulsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…Note that the feature centred at E T ~1 eV in Figure 4(a) arises from Br* products formed via photolysis of neutral (rather than cationic) ethyl bromide, and is not removed completely when 60 subtracting the "266 nm only" signal. This has been verified through VMI studies of the neutral dissociation products in separate experiments -as reported also by Tang et al 41 This feature is henceforth ignored when discussing the cation fragmentation.…”
Section: Energetically Accessible Photofragmentation Pathwayssupporting
confidence: 64%
See 1 more Smart Citation
“…Note that the feature centred at E T ~1 eV in Figure 4(a) arises from Br* products formed via photolysis of neutral (rather than cationic) ethyl bromide, and is not removed completely when 60 subtracting the "266 nm only" signal. This has been verified through VMI studies of the neutral dissociation products in separate experiments -as reported also by Tang et al 41 This feature is henceforth ignored when discussing the cation fragmentation.…”
Section: Energetically Accessible Photofragmentation Pathwayssupporting
confidence: 64%
“…90 As noted earlier, C 2 H 5 X + photolysis yields one ionic and at least one neutral fragment. Neutral halogen atoms can be detected via resonance-enhanced multiphoton ionization (REMPI), [40][41][42][43] The ions were extracted through a 482 mm field-free region and velocity-map imaged onto a 40 mm position-sensitive ion detector (Photonis) consisting of a chevron pair of microchannel plates (MCPs) coupled to a P47 phosphor screen. To identify the ions formed in a given experiment, time-of-flight mass spectra 105 (TOF-MS) were recorded by stepping a 20 ns time gate across the range of arrival times of interest and logging the total ion signal recorded by the camera at each arrival time.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the time-sliced ion velocity imaging technique [4−6] combined with resonance enhanced multiphoton ionization (REMPI) is widely used to study the photodissociation of alkyl halides [7−21]. For example, CH 3 Br [14], C 2 H 5 Br [15], iso-C 3 H 7 Br [16], n-C 4 H 9 Br [17], iso-C 4 H 9 Br [18], and tert-C 4 H 9 Br [18] have been investigated by this sensitive technique. From the analysis of the photodissociation processes of alkyl bromides, different dissociation mechanisms are revealed in the previous studies [14−18].…”
Section: Introductionmentioning
confidence: 99%
“…The non-bonding electron of the halogen atom undergoes a transition to the antibonding s* orbital localized on the CÀX bond (X denotes halogen). [1][2][3][4][5][6][7][8] In contrast, the photodissociation processes for aryl halides are more complicated since more electronic states are involved, thus making multiple dissociation channels probable. [9][10][11][12][13][14][15][16][17][18][19][20] These include predissociation via intersystem crossing (ISC), hot molecular dissociation via internal conversion, and direct photodissociation from a repulsive surface.…”
Section: Introductionmentioning
confidence: 99%